FORMATION OF STUDENTS' ISLAMIC CHARACTER THROUGH LIVING HADITH AT MTS AL-AMIN RAYA MEDAN - Arif Rio Kari; Ahmad Darlis (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The character of students in this era of globalization has been degraded, many of which occur among students such as ignoring teachers, mocking teachers, and even worse fighting teachers. This study aims to comprehensively describe the formation of students' Islamic character through the living hadith program. This study uses a qualitative approach with a case study method. Data was collected through observation, interviews and documentation. Data analysis techniques are carried out using data reduction, data presentation, and conclusion drawn. The results of the study show that the application of living hadith is carried out through the internalization of hadith values into students' daily activities such as praying before and after studying, praying dhuha in congregation, reading surah Al-Kahfi together, infaq/almsgiving, respecting teachers and respecting time. The inhibiting factors faced include students' lack of understanding of the meaning of the hadith, and the lack of parental involvement in support programs at home. The solutions implemented include teacher training, simplification of the hadith language so that it is easy for students to understand, and strengthening the synergy between schools and parents in the formation of Islamic scripts. Thus, living hadith has proven to be one of the effective methods in shaping students' Islamic personalities, although it still needs to be strengthened in terms of implementation and cooperation to overcome various existing obstacles.